2014
DOI: 10.1111/afe.12046
|View full text |Cite
|
Sign up to set email alerts
|

The new world screwworm: prospective distribution and role of weather in eradication

Abstract: 1 The new world screwworm [Cochliomyia hominivorax (Coquerel)] was eradicated in North America, Libya and other locations using the sterile insect technique (SIT). 2 To examine the role of weather in its eradication, a physiologically-based demographic model was developed and used to characterize its range of year-round persistence. Published data on developmental times, fecundity and mortality rates on temperature were used to parameterize the model. The lower and upper thermal thresholds for development are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 71 publications
0
28
0
Order By: Relevance
“…However, the fly is endemic to the Caribbean and South America (Laake, ; Baumhover, ; Comis et al ., ) and non‐autochthonous cases of myiasis are occasionally reported in the U.S.A. (USDA‐APHIS, United States Department of Agriculture – Animal and Plant Health Inspection Service, ). Eradication of the fly cost more than 750 million US dollars (Gutierrez & Ponti, ), removing an important economic constraint on the livestock sector (Vargas‐Terán et al ., ) and infestations in wildlife. Although not completely attributable to eradication, cattle production in Texas increased from 6.53 million head in 1974 (E. S. Krafsur, personal communication) to 12.32 million in 2016 (USDA, United States Department of Agriculture, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the fly is endemic to the Caribbean and South America (Laake, ; Baumhover, ; Comis et al ., ) and non‐autochthonous cases of myiasis are occasionally reported in the U.S.A. (USDA‐APHIS, United States Department of Agriculture – Animal and Plant Health Inspection Service, ). Eradication of the fly cost more than 750 million US dollars (Gutierrez & Ponti, ), removing an important economic constraint on the livestock sector (Vargas‐Terán et al ., ) and infestations in wildlife. Although not completely attributable to eradication, cattle production in Texas increased from 6.53 million head in 1974 (E. S. Krafsur, personal communication) to 12.32 million in 2016 (USDA, United States Department of Agriculture, ).…”
Section: Introductionmentioning
confidence: 99%
“…The present study builds upon the analysis reported by Gutierrez & Ponti () concerning the role of SIT and weather on the eradication of the fly in North America. Specifically, we link the effects of the North American Monsoons (NAMS) to screwworm myiasis outbreaks, and explain why, despite massive releases of sterile adults, outbreaks of myiasis occurred during the 1962–1982 eradication period in the SW U.S.A. (Novy, ).…”
Section: Introductionmentioning
confidence: 99%
“…An increase in infestations associated with higher temperature is concerning because it has been estimated that current global change trends could result in an increase in temperatures in Uruguay of up to 3 degrees Celsius by 2100 [37]. Under this scenario that has been contemplated for other parts of the American continent [38], the risk for screwworm infestation could extend in the year thereby reducing the e cacy of seasonal birthing currently practiced by livestock producers in parts of Uruguay with a more temperate climate to reduce screwworm cases. The apparent seasonality of myiases in feral swine mirrors prevalence patterns in livestock, which suggests that screwworms could persist in the environment by infesting feral swine alone in in Uruguay, which was documented in Florida before population control of feral swine and screwworm eradication took place.…”
Section: Discussionmentioning
confidence: 99%
“…PBDMs often include bottom‐up effects of host plant growth and development on pest dynamics and, in some cases, the top‐down action of natural enemies (see Gutierrez et al ., 2010b; Gutierrez & Ponti, 2014b). The models may also be used for studies of medical and veterinary pests (e.g., Gutierrez & Ponti, 2014a). When driven by weather including climate change scenarios, PBDMs predict the phenology, age structure and abundance dynamics, and distribution of the interacting species across wide geographic areas (e.g., Gutierrez et al ., ; Gutierrez & Ponti, ).…”
Section: A Physiologically Based Approach To Pest Risk Assessmentmentioning
confidence: 99%
“…GRASS GIS, see Neteler et al, 2012). Some recent examples are Gutierrez et al (2005) and Gutierrez & Ponti (2011, 2014a. This paper illustrates how PBDMs can streamline pest risk assessment by providing a process-based guide to identify knowledge gaps, and guide the collection of the data required to develop the PBDM to determine whether a species should or should not be considered a current or potential pest in a region.…”
Section: Introductionmentioning
confidence: 99%